Research on component synthesis active vibration suppression method for flexible spacecraft attitude maneuver with reaction jet actuators. Issue 2 (22nd January 2020) - Xu, Jiangtao; Luo, Na; Liu, Shaojie; Zhao, Baoshan; Qi, Fang; Lian, Yinjun; Wang, Litong
Abstract : Purpose: The purpose of this paper is to design a component synthesis method to suppress the vibration of the flexible spacecraft, which has the constant amplitude force/moment actuator. Design/methodology/approach: The authors proposed a method to construct constant amplitude of time delay and composite coefficient sequences based on the principles of the component synthesis vibration suppression (CSVS). The associated design strategy of the CSVS torque control is also developed. The dynamic model consisting of a single axis rotating rigid central body and a fixed flexibility panel is used to validate the proposed method. Constraint modal and free modal method are both tested to analyse the natural frequencies of the panel and dynamic properties of rigid–flexible decoupling system, under the conditions of known and unknown frequencies. The feasibility of constructing CSVS control force based on the constraint modal frequency is also analysed. Findings: The proposed method can suppress multistage vibration and has arbitrary order robustness for each order frequencies simultaneously. Simulation results show that only the duration time of the actuator has to be set for the proposed method, reasonable vibration suppression effect can be achieved. Practical implications: The method can be used in spacecraft, especially flexible spacecraft to suppress the vibration; the approach is convenient for engineering application and can be easily designed. Originality/value: The authors proposed a method to construct constant amplitude of time delay and composite coefficient sequences based on the principles of the CSVS.